Carbon black, slurry and lithium-ion secondary battery
Carbon black with specific surface area and DBP/CDBP ratio optimizes slurry viscosity and dispersion, addressing conductive path formation issues in lithium ion batteries, enhancing battery performance.
Patent Information
- Application Number
- CN202180075059.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-04
- Filing Date
- 2021-12-02
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-12-02
AI Technical Summary
The reduction of conductive agent proportion in lithium ion secondary batteries leads to difficulties in forming conductive paths, increased slurry viscosity, and poor dispersion, which affects conductivity and discharge capacity.
Carbon black with a specific surface area of 150-400 m²/g and a DBP/CDBP ratio of 2.0 or less, combined with a low ash and iron content, is used to create a slurry with controlled viscosity and improved dispersion, enhancing conductivity and battery performance.
The carbon black achieves low viscosity slurry formation, maintaining high conductivity and preventing local conductivity reduction, thereby improving battery capacity and cycle characteristics.
Smart Images

Figure BDA0004212642520000181 
Figure BDA0004212642520000191
Abstract
Description
Technical Field
[0001] The invention relates to carbon black, slurry and lithium ion secondary battery. Background Art
[0002] Lithium ion secondary batteries are widely used as power sources for small electronic devices such as smartphones and tablet computers. Lithium ion secondary batteries are generally composed of electrodes, separators, and electrolytes. For electrodes, composite material slurry obtained by dispersing active materials, conductive agents, adhesives, etc. in a dispersion medium is applied to a metal plate for a current collector and dried to form a composite material layer for manufacturing.
[0003] As the conductive agent, for example, carbon black is used (for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-193986 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The role of the conductive agent is to form a conductive path in the electrode. Therefore, if the conductive agent is accumulated in the electrode, the conductivity will be locally deteriorated, the active material will not be effectively utilized, the discharge capacity will be reduced, and the battery characteristics will be reduced.
[0009] In recent years, the high capacity of lithium ion secondary batteries is required, and there is a tendency to increase the proportion of active materials in the composite material layer and reduce the proportion of conductive agents and adhesives. If the proportion of conductive agents is reduced, the formation of conductive paths in the electrode becomes difficult, and the battery characteristics are reduced. Therefore, the following research has been carried out: using a conductive agent with a small particle size to increase the number of particles per unit mass, by shortening the distance between the conductive agents in the electrode, increasing the contact points with the active material and the collector, thereby improving the conductivity. However, if the specific surface area increases with the small particle size of the conductive agent, the viscosity of the composite material slurry increases significantly, so uniform dispersion becomes difficult.
[0010] In addition, when carbon black is used as a conductive agent, the structure of carbon black affects the conductivity and slurry viscosity. Here, the structure of carbon black refers to the structure formed by the connection of primary particles. With the reduction of the particle size of primary particles, the structure of carbon black develops in a complex and intertwined shape. If the structure develops, a conductive path can be efficiently formed in the electrode, but if the dispersion state is poor, this effect cannot be fully exerted.
[0011] In order to achieve high dispersion of the conductive agent and low viscosity of the composite material slurry, the use of high-pressure jet mills and other devices to impart strong collision energy for dispersion and extend the dispersion treatment time have been studied, but there are problems such as impurities being mixed in due to wear of the device. In addition, the addition of dispersants has been studied, but if the amount of dispersants added is increased due to the small particle size of the conductive agent, there is a problem of reducing battery characteristics.
[0012] Therefore, an object of the present invention is to provide a novel carbon black having a high specific surface area and capable of forming a slurry with a low viscosity. Another object of the present invention is to provide a slurry containing the carbon black and a lithium ion secondary battery containing the carbon black.
[0013] Means for solving problems
[0014] The inventors of the present application conducted intensive studies to solve the above-mentioned problems and found that, for carbon black having a high specific surface area, the ratio of DBP absorption to compressed DBP absorption significantly affects slurry viscosity.
[0015] That is, the present invention for solving the above-mentioned problems is as follows.
[0016] (1) Carbon black, with a specific surface area of 150 m 2 / g above 400m 2 / g or less, and the ratio of DBP absorption (DBP) to compressed DBP absorption (CDBP) (DBP / CDBP) is 2.0 or less.
[0017] (2) The carbon black as described in (1), wherein the DBP absorption of the carbon black is 200 mL / 100 g or more and 350 mL / 100 g or less.
[0018] (3) The carbon black as described in (1) or (2), wherein the ash content of the carbon black is 0.02 mass % or less.
[0019] (4) The carbon black as described in any one of (1) to (3), wherein the iron content is less than 2000 ppb by mass.
[0020] (5) A slurry comprising the carbon black according to any one of (1) to (4) and a dispersion medium.
[0021] (6) The slurry as described in (5), wherein the slurry is heated at 25°C and a shear rate of 10 s -1 The viscosity under the conditions is 200 mPa·s or more and 1200 mPa·s or less.
[0022] (7) A lithium ion secondary battery comprising a positive electrode, a negative electrode and a separator, wherein at least one of the positive electrode and the negative electrode contains the carbon black according to any one of (1) to (4).
[0023] Effects of the Invention
[0024] According to the present invention, a novel carbon black having a high specific surface area and capable of forming a slurry with a low viscosity can be provided. In addition, according to the present invention, a slurry containing the carbon black and a lithium ion secondary battery containing the carbon black can be provided. DETAILED DESCRIPTION
[0025] Hereinafter, the preferred embodiments of the present invention will be described in detail. It should be noted that the present invention is not limited to the embodiments described below. It should be noted that in this specification, unless otherwise specified, the numerical range represented by "~" means the range of the numerical value "above" on the left and "below" on the right. For example, "A~B" means above A and below B.
[0026] <Carbon black>
[0027] The carbon black of this embodiment has 150 m 2 / g above 400m 2 / g or less. This specific surface area is higher than the specific surface area of carbon black used as a conductive agent for lithium ion secondary batteries in the past. The conductivity imparting ability of carbon black with such a high specific surface area becomes higher due to the percolation effect in the matrix, so it is effective as a conductive agent.
[0028] In addition, the specific surface area is measured according to the A method flow method (thermal conductivity measurement method) of JIS K6217-2:2017.
[0029] If the specific surface area of carbon black is less than 150m 2 / g, the contact points with the active material in the composite material layer will decrease, and sometimes the conductivity cannot be fully exerted. From the viewpoint of further improving the conductivity imparting ability, the specific surface area of carbon black is preferably 160m 2 / g or more, more preferably 180m 2 / g or more, more preferably 200m 2 That is, the specific surface area of carbon black can be, for example, 150 to 400 m 2 / g, 160~400m 2 / g, 180~400m 2 / g or 200~400m 2 / g. In addition, if the specific surface area of carbon black exceeds 400m 2 / g, the dispersion in the slurry becomes significantly difficult, and the conductivity deteriorates locally in the electrode, which may reduce the battery characteristics. The specific surface area of carbon black can be increased by reducing the primary particle size, hollowing, and making the particle surface porous.
[0030] In the carbon black of the present embodiment, the ratio (DBP / CDBP) of the DBP absorption (DBP) to the compressed DBP absorption (CDBP) is 2.0 or less.
[0031] DBP absorption (DBP) is an index for evaluating the ability of carbon black to absorb dibutyl phthalate in the voids formed by the particle surface and structure. In this specification, DBP absorption refers to the value obtained by converting the value measured by the method described in Method B of JIS K6221 into a value equivalent to JIS K6217-4:2008 using the following formula (a).
[0032] DBP absorption = (A-10.974) / 0.7833…(a)
[0033] [In the formula, A represents the value of DBP absorption measured by the method described in JIS K6221.]
[0034] In the measurement of DBP absorption (DBP), agglomerates (secondary aggregation of structures) of carbon black are crushed by applying a strong external force, and the surface area of primary particles and the degree of structural development can be evaluated.
[0035] The compression DBP absorption (CDBP) is the DBP absorption measured after the carbon black is compressed in advance to destroy the structure, and is an indicator of the mechanical strength of the structure. It can be measured in accordance with JIS K6217-4:2008. Specifically, the sample is placed in a hydraulic cylinder, compressed at 165 MPa for 1 second, and then the sample is taken out and the sample block is sieved to reach less than 0.25 cm. After repeating this series of operations 4 times, the DBP absorption is measured, and the compression DBP absorption (CDBP) can be obtained.
[0036] The inventors of the present application conducted in-depth research to solve the above-mentioned problems and found that, for carbon black having a high specific surface area, the ratio of DBP absorption to compressed DBP absorption (DBP / CDBP) greatly affects the slurry viscosity. That is, the carbon black of the present embodiment can achieve a sufficiently low slurry viscosity while having a high specific surface area by making the ratio (DBP / CDBP) less than 2.0.
[0037] For carbon black, the shape and strength of the structure vary greatly depending on the thermal history during synthesis (for example, the thermal history caused by the thermal decomposition and combustion reaction of the fuel oil, the thermal decomposition and combustion reaction of the raw materials, the rapid cooling and reaction cessation caused by the cooling medium, etc.), the collision frequency of the primary particles, etc.
[0038] According to the inventors of the present application, when comparing carbon blacks with the same specific surface area, the carbon black with a ratio (DBP / CDBP) of less than 2.0 has a lower slurry viscosity than the carbon black with a ratio (DBP / CDBP) of more than 2.0. Here, a lower ratio (DBP / CDBP) means less structural damage caused by external forces. For the carbon black of this embodiment, it is believed that during the preparation of the slurry, since there is less structural damage caused by external forces, the newly generated highly active surface due to the damage is reduced, the re-aggregation of carbon black is less likely to occur, and the slurry viscosity is reduced.
[0039] In this embodiment, by the ratio (DBP / CDBP) being less than 2.0, even carbon black with a small particle size, a high specific surface area, and a developed structure can reduce uneven coating of the collector and the bias of the material in the electrode caused by the increase in the viscosity of the composite material slurry. In addition, by making the dispersion state and contact state of the active material and the conductive agent in the electrode good, it is possible to suppress the reduction of local conductivity and the reduction of battery discharge capacity, and to achieve high capacity of lithium ion secondary batteries.
[0040] In the carbon black of the present embodiment, from the viewpoint of more significantly exerting the above-mentioned effect, the ratio (DBP / CDBP) is preferably 1.9 or less, more preferably 1.8 or less, and even more preferably 1.7 or less.
[0041] For the carbon black of the present embodiment, if the ratio (DBP / CDBP) is too small, the mechanical strength of the structure is too strong or the structure is in a shape that is not easily destroyed, so there is a situation in which the slurry viscosity increases due to excessive development of agglomerates during slurry preparation. From the viewpoint of suppressing the excessive development of the agglomerates, the ratio (DBP / CDBP) is preferably 1.0 or more, more preferably 1.1 or more, further preferably 1.2 or more, more preferably 1.3 or more, and particularly preferably 1.4 or more. That is, the ratio (DBP / CDBP) may be, for example, 1.0 to 2.0, 1.0 to 1.9, 1.0 to 1.8, 1.0 to 1.7, 1.1 to 2.0, 1.1 to 1.9, 1.1 to 1.8, 1.1 to 1.7, 1.2 to 2.0, 1.2 to 1.9, 1.2 to 1.8, 1.2 to 1.7, 1.3 to 2.0, 1.3 to 1.9, 1.3 to 1.8, 1.3 to 1.7, 1.4 to 2.0, 1.4 to 1.9, 1.4 to 1.8, or 1.4 to 1.7.
[0042] The DBP absorption of the carbon black of the present embodiment may be, for example, 180 mL / 100 g or more, preferably 190 mL / 100 g or more, and more preferably 200 mL / 100 g or more. In addition, the DBP absorption of the carbon black of the present embodiment may be, for example, 370 mL / 100 g or less, and more preferably 350 mL / 100 g or less. That is, the DBP absorption of the carbon black of the present embodiment may be, for example, 180 to 370 mL / 100 g, 180 to 350 mL / 100 g, 190 to 370 mL / 100 g, 190 to 350 mL / 100 g, 200 to 370 mL / 100 g, or 200 to 350 mL / 100 g.
[0043] In carbon black with developed structure, the gaps formed in the necks formed by the fusion of primary particles and between particles increase, so the DBP absorption increases. If the DBP absorption is too small, the conductivity-imparting ability in the electrode may be reduced due to insufficient development of the structure. In addition, the volume change of the active material accompanying the charge and discharge of the lithium-ion secondary battery may not be buffered, and the battery characteristics such as the cycle characteristics may be reduced. If the DBP absorption is too large, the binder in the composite material layer may be captured by the structure of the carbon black, and the adhesion with the active material and the collector may be reduced, and the battery characteristics may be reduced.
[0044] The average primary particle size of the carbon black of the present embodiment can be, for example, less than 35 nm, preferably less than 30 nm, and more preferably less than 25 nm. According to the opinion of the inventors of the present application, among the carbon blacks satisfying the above-mentioned ratio (DBP / CDBP), when two types having the same specific surface area but different average primary particle sizes are compared, the slurry viscosity of the carbon black with a small particle size becomes lower. It is believed that this is because: in the carbon black with a large particle size, the specific surface area becomes higher by making the surface porous, while on the other hand, in the carbon black with a small particle size, it is believed that the carbon black with a relatively smooth surface constitutes a complex structure to achieve a high specific surface area, and the above-mentioned effect brought about by the structural strength represented by the ratio (DBP / CDBP) is more significantly exerted.
[0045] In the past, for the carbon black of the conductive agent used for lithium ion secondary batteries, if the average primary particle size is small (for example, less than 30nm), slurrying is difficult, but the carbon black of the present embodiment satisfies the above ratio (DBP / CDBP), so even when the average primary particle size is small (for example, less than 30nm), slurrying is possible. Like this, by making the use of small particle size carbon black possible, even if the matching ratio in the composite material layer is low, high conductivity can be exerted. The average primary particle size of carbon black can be, for example, more than 1nm, more than 5nm, or more than 10nm. That is, the average primary particle size of carbon black can be, for example, more than 1nm and less than 35nm, more than 1nm and less than 30nm, more than 1nm and less than 25nm, more than 5nm and less than 35nm, more than 5nm and less than 30nm, more than 5nm and less than 25nm, more than 10nm and less than 35nm, more than 10nm and less than 30nm or more than 10nm and less than 25nm.
[0046] The average primary particle size of carbon black can be obtained by measuring the primary particle sizes of more than 100 carbon black particles randomly selected from a 50,000-fold magnified image of a transmission electron microscope (TEM) and calculating the average value. The primary particles of carbon black are close to a perfect sphere with a small aspect ratio, but are not perfect spheres. Therefore, in this embodiment, the maximum length of the line segment connecting two points on the periphery of the primary particle in the TEM image is taken as the primary particle size of carbon black.
[0047] The ash content of the carbon black of the present embodiment may be, for example, 0.05 mass % or less, preferably 0.03 mass % or less, and more preferably 0.02 mass % or less. The ash content can be measured according to JIS K1469:2003 and can be reduced by classifying the carbon black using a dry cyclone separator or the like.
[0048] The iron content of the carbon black of the present embodiment may be, for example, less than 2500 mass ppb, preferably less than 2300 mass ppb, and more preferably less than 2000 mass ppb. The iron content can be reduced by, for example, bringing the carbon black into contact with a magnet.
[0049] The iron content of carbon black can be measured by high-frequency inductively coupled plasma mass spectrometry after pretreatment by an acid decomposition method according to JIS K0116:2014. Specifically, it can be measured by the following method. First, accurately weigh 1 g of carbon black in a quartz beaker, and heat it at 800°C × 3 hr in an air atmosphere using an electric furnace. Then, add 10 mL of a mixed acid (70% by mass of hydrochloric acid, 30% by mass of nitric acid) and more than 10 mL of ultrapure water to the residue, and heat and dissolve it on a hot plate at 200°C × 1 hr. After cooling, use a high-frequency inductively coupled plasma mass spectrometer (Agilent 8800 manufactured by Agilent) to measure the solution diluted with ultrapure water and adjusted to 25 mL.
[0050] If the carbon black of the present embodiment has a low ash and iron content, the mixing of foreign matter such as metal and ceramics caused by damage to the device can be more significantly suppressed during the mixing process. In addition, the reduction in conductivity in the electrode caused by the mixing of ash, insulating foreign matter, etc. can also be suppressed. Therefore, the carbon black of the present embodiment with a low ash and iron content can be preferably used in lithium ion secondary batteries that require high safety.
[0051] The method for producing carbon black of the present embodiment is not particularly limited. For example, raw materials such as hydrocarbons can be supplied from a nozzle disposed in the upstream portion of a reactor, carbon black can be produced through thermal decomposition reaction and / or combustion reaction, and captured from a bag filter directly connected to the downstream portion of the reactor.
[0052] The raw materials used are not particularly limited, and gaseous hydrocarbons such as acetylene, methane, ethane, propane, ethylene, propylene, butadiene, and oily hydrocarbons such as toluene, benzene, xylene, gasoline, kerosene, light oil, and heavy oil can be used. Among them, acetylene with few impurities is preferably used. The decomposition heat of acetylene is greater than that of other raw materials, and the temperature in the reactor can be increased. Therefore, the nucleation of carbon black is superior to the particle growth caused by the addition reaction, and the primary particle size of carbon black can be reduced. In addition, the inventors of the present application have conducted in-depth research to control the structural strength of carbon black, and found that it is effective to use a variety of raw materials and supply them to the reactor after heating the raw materials. In the previous preparation method, the carbon black generated through the high temperature part of the reactor and the carbon black generated through the low temperature part are mixed, and the deviation in characteristics is also large, but by using a variety of raw materials, the temperature in the reactor becomes uniform, and the reaction process of thermal decomposition and combustion becomes uniform, so it is believed that the structural strength of carbon black is uniform and the destruction of the weak part is reduced. In addition, it is believed that the mixing of a variety of raw materials is promoted by heating the raw materials, and a more uniform temperature field can be formed. The plurality of raw materials are preferably mixed before being supplied to the reactor. When oily hydrocarbons are used, they are preferably supplied after being gasified by heating. The heating method is not particularly limited, and for example, the tank or the transport piping can be heated by heat exchange with a heat medium.
[0053] In addition, it is preferred to supply oxygen, hydrogen, nitrogen, water vapor, etc. to the reactor separately relative to the raw materials that become the carbon source. Gases other than these raw materials promote gas stirring in the reactor, increase the frequency of collision and fusion of primary particles of carbon black generated from the raw materials, and therefore, by using gases other than the raw materials, the structure of carbon black develops, and the DBP absorption tends to increase. As a gas other than the raw material, oxygen is preferably used. If oxygen is used, part of the raw material is burned, the temperature in the reactor becomes higher, and it is easy to obtain carbon black with a small particle size and a high specific surface area. As a gas other than the raw material, a variety of gases can also be used. The supply position of the gas other than the raw material is preferably the upstream part of the reactor, and it is preferably supplied from a nozzle other than the raw material. As a result, the stirring of the raw material also supplied from the upstream part occurs efficiently, and the structure becomes easy to develop.
[0054] In the previous carbon black manufacturing, considering the thermal decomposition of the raw materials and the cessation of the combustion reaction, a cooling medium such as water is sometimes introduced from the downstream part of the reactor, but no effect on the structural development is found. On the other hand, the deviation of the structural strength may become larger due to the rapid temperature change and the ratio (DBP / CDBP) may become lower. Therefore, in the present embodiment, it is preferred not to introduce a cooling medium from the downstream part of the reactor.
[0055] <Slurry>
[0056] The slurry of the present embodiment contains the carbon black of the present embodiment and a dispersion medium.
[0057] If the viscosity of the slurry is too high, strong shear is applied when mixing with the active material, so sometimes the structure of the carbon black is destroyed and the conductivity is reduced, and foreign matter is mixed in due to the wear of the device. On the other hand, if the viscosity of the slurry is too low, sometimes the carbon black is easily precipitated in the slurry, and it becomes difficult to maintain uniformity. In this embodiment, since the above-mentioned carbon black is used, the viscosity of the slurry can be reduced, so the destruction of the carbon black structure is significantly suppressed, and the excellent conductivity imparting ability can be maintained. In addition, the mixing of foreign matter caused by the wear of the equipment is significantly suppressed. That is, in this embodiment, the mixing ratio of the active material in the composite material layer can be increased without damaging the viscosity characteristics and conductivity of the slurry, and the high capacity of the lithium-ion secondary battery can be achieved.
[0058] From the viewpoint of obtaining the above-mentioned effect more significantly, the slurry viscosity (25°C, shear rate 10s -1 ) is preferably 100 mPa·s or more, more preferably 200 mPa·s or more. As a result, the sedimentation of carbon black is suppressed. The uniformity of the slurry is improved. In addition, from the perspective of more significantly obtaining the above-mentioned effect, the slurry viscosity (25°C, shear rate 10s -1) is preferably 1500 mPa·s or less, more preferably 1200 mPa·s or less. That is, the slurry viscosity (25°C, shear rate 10s -1 ) can be, for example, 100 to 1500 Pa·s, 100 to 1200 Pa·s, 200 to 1500 Pa·s or 200 to 1200 Pa·s.
[0059] The dispersion medium is not particularly limited, and for example, N-methyl-2-pyrrolidone, ethanol, ethyl acetate, etc. can be used.
[0060] The slurry of the present embodiment may further contain other carbon black, graphite, carbon nanotubes, carbon nanofibers, etc. within a range that does not impair the conductivity-imparting ability and dispersibility of the carbon black of the present embodiment.
[0061] The slurry of this embodiment may further contain additives such as an active material and a dispersant.
[0062] In the slurry of the present embodiment, the content of the carbon black of the present embodiment may be, for example, 0.5% by mass or more, preferably 1% by mass or more. In addition, in the slurry of the present embodiment, the content of the carbon black of the present embodiment may be, for example, 50% by mass or less, preferably 20% by mass or less. That is, in the slurry of the present embodiment, the content of the carbon black of the present embodiment may be, for example, 0.5 to 50% by mass, 0.5 to 20% by mass, 1 to 50% by mass, or 1 to 20% by mass.
[0063] The method for preparing the slurry of the present embodiment is not particularly limited, and the slurry can be prepared by kneading the components using, for example, a general device such as a mixer, a kneader, a disperser, a mill, or an automatic orbiting rotary device.
[0064] The slurry of the present embodiment can be preferably used as an electrode-forming slurry for forming an electrode of a lithium-ion secondary battery. The electrode-forming slurry may be a positive electrode-forming slurry or a negative electrode-forming slurry.
[0065] When the slurry of the present embodiment is a slurry for electrode formation, the slurry of the present embodiment may contain an active material, a conductive agent, and a dispersion medium. In this case, the slurry contains the carbon black of the present embodiment as a conductive agent.
[0066] The content of the conductive agent in the electrode forming slurry can be, for example, 0.01% by mass or more, preferably 0.05% by mass or more, and more preferably 0.08% by mass or more. In addition, the content of the conductive agent in the electrode forming slurry can be, for example, 20% by mass or less, preferably 15% by mass or less, and more preferably 10% by mass or less. That is, the content of the conductive agent in the electrode forming slurry can be, for example, 0.01-20% by mass, 0.01-15% by mass, 0.01-10% by mass, 0.05-20% by mass, 0.05-15% by mass, 0.05-10% by mass, 0.08-20% by mass, 0.08-15% by mass, or 0.08-10% by mass.
[0067] The electrode forming slurry may further contain a conductive agent other than carbon black. Examples of the conductive agent other than carbon black include graphite, carbon nanotubes, and carbon nanofibers.
[0068] In the electrode forming slurry, the proportion of carbon black in the conductive agent may be, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, or may be 100% by mass.
[0069] The active material is not particularly limited, and known active materials for lithium ion secondary batteries can be used without particular restrictions. As positive electrode active materials, for example, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel manganese cobalt oxide, lithium iron phosphate, etc. can be cited. As negative electrode active materials, natural graphite, artificial graphite (Japanese: artificial black lead), graphite (グラファイト), activated carbon, coke, needle coke, sulfide coke, mesophase carbon microspheres (Japanese: メソフェーズマイクロビーズ), carbon fiber, pyrolytic carbon and other carbonaceous materials can be cited.
[0070] The electrode forming slurry may further contain a binder. The binder is not particularly limited, and known binders for lithium ion secondary batteries can be used without particular limitation. Examples of the binder include polyethylene, nitrile rubber, polybutadiene, butyl rubber, polystyrene, styrene-butadiene rubber, polysulfide rubber, nitrocellulose, carboxymethyl cellulose, polyvinyl alcohol, tetrafluoroethylene resin, polyvinylidene fluoride, polychloroprene fluoride, and the like.
[0071] The method for forming an electrode using the electrode-forming slurry is not particularly limited. For example, by applying the electrode-forming slurry on a current collector and drying it, an electrode including a current collector and a composite material layer can be formed.
[0072] The current collector is not particularly limited, and for example, metal foils of gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, titanium, and alloys thereof as main components are used. For example, aluminum foil is preferably used as the positive electrode current collector, and copper foil is preferably used as the negative electrode current collector.
[0073] <Lithium-ion secondary battery>
[0074] The lithium ion secondary battery of the present embodiment has a positive electrode, a negative electrode and a separator. In addition, at least one of the positive electrode and the negative electrode of the lithium ion secondary battery of the present embodiment contains the carbon black of the present embodiment described above. At least one of the positive electrode and the negative electrode of the lithium ion secondary battery of the present embodiment may also be formed by the above-mentioned electrode forming slurry, and at least one of the positive electrode and the negative electrode may also include a composite material layer formed by the above-mentioned electrode forming slurry on the collector.
[0075] The lithium ion secondary battery of the present embodiment has a high capacity because the carbon black of the present embodiment is used, and can be manufactured with good productivity by using the above-mentioned electrode forming slurry.
[0076] The lithium ion secondary battery of this embodiment preferably has a positive electrode containing the carbon black of this embodiment. In addition, the lithium ion secondary battery of this embodiment preferably has a positive electrode formed of the electrode forming slurry, and more preferably has a composite material layer formed of the electrode forming slurry on a current collector.
[0077] The lithium ion secondary battery of the present embodiment may have the same structure as that of a known lithium ion secondary battery except for the electrode containing the carbon black of the present embodiment.
[0078] The separator is not particularly limited, and known separators can be used as separators for lithium ion secondary batteries without particular limitation. As separators, synthetic resins such as polyethylene and polypropylene can be cited, for example. From the aspect of good retention of the electrolyte, the separator is preferably a porous film.
[0079] The lithium ion secondary battery of the present embodiment may include an electrode group in which a positive electrode and a negative electrode are stacked or wound with a separator interposed therebetween.
[0080] The lithium ion secondary battery of this embodiment may be formed by immersing the positive electrode, the negative electrode, and the separator in the electrolyte solution.
[0081] The electrolyte is not particularly limited, and for example, can be a non-aqueous electrolyte containing a lithium salt. As the non-aqueous solvent in the non-aqueous electrolyte containing a lithium salt, ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, etc. can be cited. In addition, as the lithium salt that can be dissolved in the non-aqueous solvent, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, etc. can be cited.
[0082] The lithium ion secondary battery of the present embodiment may use an ion conductive polymer or the like as an electrolyte.
[0083] As mentioned above, although the preferred embodiment of the present invention was described, the present invention is not limited to the above-mentioned embodiment.
[0084] For example, one aspect of the present invention may be a specific surface area of 150 m 2 / g above 400m 2 / g or less of carbon black. The evaluation method may include: a measurement step of determining the ratio (DBP / CDBP) of DBP absorption (DBP) to compressed DBP absorption (CDBP); and an evaluation step of evaluating carbon black using the ratio (DBP / CDBP).
[0085] The evaluation step may be a screening step of screening carbon blacks having a ratio (DBP / CDBP) of 2.0 or less. In this case, the above-mentioned evaluation method may also be referred to as a screening method for carbon blacks.
[0086] Example
[0087] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0088] (Example 1)
[0089] <Manufacturing of Carbon Black>
[0090] The nozzle installed in the upstream part of the carbon black reaction furnace (furnace length 6m, furnace diameter 0.65m) was used to generate 12Nm 3 / h supply of acetylene as raw material, 32kg / h supply of toluene, and 20Nm 3 / h is used to supply oxygen as a gas other than the raw material to produce carbon black, and the oxygen is captured by a bag filter installed in the downstream part of the reactor. Then, it is passed through a dry cyclone separator device and a magnet for iron removal and recovered in a tank. It should be noted that acetylene, toluene and oxygen are supplied to the reactor after being heated to 115°C. The following physical properties of the obtained carbon black are measured. The evaluation results are shown in Table 1.
[0091] (1) Specific surface area
[0092] The thermal conductivity was measured according to the A method flow method (thermal conductivity measurement method) of JIS K6217-2:2017.
[0093] (2) DBP absorption: The value measured by the method described in Method B of JIS K6221 was converted into a value equivalent to JIS K6217-4:2008 using the above formula (a).
[0094] (3) Compressive DBP absorption (CDBP): A sample was prepared in accordance with JIS K6217-4:2008 Supplementary Book A (Preparation method of compression sample, using compression apparatus type I), and the measurement was performed in accordance with JIS K6217-4:2008.
[0095] (4) Average primary particle size: The primary particle sizes of 100 or more carbon black particles randomly selected from a 50,000-times-magnification image of a transmission electron microscope were measured, and the average value was calculated.
[0096] (5) Ash content: measured in accordance with JIS K1469:2003.
[0097] (6) Iron content: The iron content was measured by high-frequency inductively coupled plasma mass spectrometry after pretreatment by an acid decomposition method in accordance with JIS K0116:2014.
[0098] <Preparation of slurry>
[0099] 3 parts by mass of carbon black and 97 parts by mass of N-methyl-2-pyrrolidone (manufactured by Kanto Chemical Co., Ltd.) as a dispersion medium were kneaded at a rotation speed of 2000 rpm for 30 minutes using a rotary mixer ("Thinky Mixer ARV-310" manufactured by Thinky Co., Ltd.) to prepare a carbon black slurry. The carbon black slurry was prepared using a viscoelasticity tester ("MCR102" manufactured by Anton Paar Co., Ltd., The viscosity of the slurry at 25°C was evaluated using a cone plate with an angle of 3° and a gap of 1 mm. The shear rate was changed from 0.01 s -1 Change to 100s -1 And measure and find the shear rate 10s -1 The results are shown in Table 2.
[0100] <Battery production>
[0101] 40 parts by mass of carbon black slurry (1.2 parts by mass of carbon black, 38.8 parts by mass of N-methyl-2-pyrrolidone), LiNi 0.5 Mn 0.3 Co 0.2O2 (Umicore "TX10") 96.8 parts by mass, polyvinylidene fluoride (Arkema "HSV900") as a binder 2 parts by mass, polyvinyl alcohol (Denka "B05") as a dispersant 0.1 parts by mass, N-methyl-2-pyrrolidone (Kanto Chemical Co., Ltd.) as a dispersion medium 10 parts by mass using a self-rotating revolution mixer (Thinky "Thinky Mixer ARV-310") at a speed of 2000rpm for 10 minutes to make a composite material slurry for positive electrode formation. The obtained composite material slurry for positive electrode formation is applied to an aluminum foil (UACJ) with a thickness of 15 μm using an applicator and pre-dried at 105 ° C for 1 hour. Then, a roller press is used to press at a linear pressure of 200 kg / cm, and the sum of the thickness of the aluminum foil and the coating film is prepared to be 80 μm. In order to remove volatile components, vacuum drying was performed at 170° C. for 3 hours to prepare a positive electrode.
[0102] Weigh 97 parts by mass of artificial graphite (manufactured by Hitachi Chemical Co., Ltd., "MAG-D") as the negative electrode active material, 2 parts by mass of styrene butadiene rubber (manufactured by Zeon Co., Ltd., "BM-400B") as a binder, and 1 part by mass of carboxymethyl cellulose (manufactured by Daicel Co., Ltd., "D2200") as a dispersant, add pure water and use a self-rotating revolution mixer (manufactured by Thinky Co., Ltd., Thinky Mixer ARV-310) to mix to make a composite material slurry for negative electrode formation. The obtained composite material slurry for negative electrode formation is applied to a copper foil (manufactured by UACJ Co., Ltd.) with a thickness of 10 μm using an applicator and pre-dried at 60 ° C for 1 hour. Then, it is pressed with a linear pressure of 100 kg / cm using a roller press, and is prepared in a manner such that the sum of the thickness of the copper foil and the coating film is 40 μm. In order to completely remove moisture, vacuum drying is performed at 120 ° C for 3 hours to make the negative electrode.
[0103] The positive electrode was processed into 40×40 mm, the negative electrode was processed into 44×44 mm, and a polyolefin microporous membrane as a separator was arranged between the two electrodes to make a battery. The electrolyte used was a solution obtained by dissolving 1 mol / L of lithium hexafluorophosphate (manufactured by Stella Chemifa) in a solution obtained by mixing ethylene carbonate (manufactured by Aldrich) and dimethyl carbonate (manufactured by Aldrich) in a volume ratio of 1 / 1.
[0104] As a discharge test of the battery, the manufactured battery was charged at 4.35V and 0.2C with a constant current and constant voltage at 25°C, and then discharged to 3.0V with a constant current of 0.2C. Then, the discharge current was changed to 0.2C, 0.5C, 1C, 2C, and 3C, and the discharge capacity relative to each discharge current was measured. The capacity retention rate at 3C discharge relative to 0.2C discharge was calculated and evaluated as the discharge rate characteristic. In addition, the manufactured battery was charged at 4.35V and 1C with a constant current and constant voltage at 25°C, and then discharged to 3.0V with a constant current of 1C. Then, the above charge and discharge were repeated for 500 cycles, and the discharge capacity was measured. The capacity retention rate at 500 cycle discharge relative to 1 cycle discharge was calculated and evaluated as the cycle characteristic. The measurement results are shown in Table 2.
[0105] (Examples 2 to 4)
[0106] Change the oxygen supply to 21 Nm 3 / h (Example 2), 22Nm 3 / h (Example 3) or 24Nm 3 / h (Example 4), except that the carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. In addition, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0107] (Example 5)
[0108] The temperature during the supply of toluene was changed to 100°C, and the supply amount of oxygen was changed to 21 Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0109] (Example 6)
[0110] The supply temperatures of acetylene and toluene were changed to 85°C and 100°C, respectively, and the supply rate of oxygen was changed to 21 Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0111] (Example 7)
[0112] The supply temperatures of acetylene and toluene were changed to 85°C and 85°C, respectively, and the supply rate of oxygen was changed to 21 Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0113] (Example 8)
[0114] Change the acetylene supply to 11 Nm 3 / h, the toluene supply rate was changed to 30kg / h, and the oxygen supply rate was changed to 19Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0115] (Example 9)
[0116] Change the acetylene supply to 13 Nm 3 / h, the toluene supply rate was changed to 35kg / h, and the oxygen supply rate was changed to 26Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0117] (Example 10)
[0118] Replace acetylene with 12Nm 3 / h of ethylene heated to 115°C and supplied, and the oxygen supply rate was changed to 22 Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0119] (Example 11)
[0120] 32 kg / h of benzene heated to 115°C was supplied instead of toluene, and the oxygen supply rate was changed to 21 Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0121] (Comparative Example 1)
[0122] Replace oxygen with 21Nm 3Carbon black was produced and evaluated in the same manner as in Example 1 except that hydrogen was heated to 115° C. / h and supplied. The results are shown in Table 1. Also, slurry and battery were produced and evaluated in the same manner as in Example 1 using the obtained carbon black. The results are shown in Table 2.
[0123] (Comparative Example 2)
[0124] Change the acetylene supply to 11 Nm 3 / h, the toluene supply rate was changed to 30kg / h, and the oxygen supply rate was changed to 24Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0125] (Example 12)
[0126] The carbon black obtained in Comparative Example 1 was subjected to oxidation treatment in an electric furnace heated to 720° C. to obtain carbon black. The obtained carbon black was evaluated in the same manner as in Example 1. The results are shown in Table 1. In addition, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0127] (Example 13)
[0128] Change the oxygen supply to 21 Nm 3 / h, and the classification conditions of the dry cyclone separator were changed to adjust the ash content. Carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. In addition, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0129] (Example 14)
[0130] Change the oxygen supply to 21 Nm 3 / h, and the magnetic flux density of the iron removal magnet was changed to adjust the iron content, and carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. In addition, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0131] (Comparative Example 3)
[0132] Change the acetylene supply to 38 Nm 3 / h, toluene was not supplied, and the oxygen supply was changed to 10 Nm 3 / h, except that the above conditions were met, carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. Also, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0133] (Comparative Example 4)
[0134] Change the oxygen supply to 22 Nm 3 / h, and the temperature during the supply of acetylene, the temperature during the supply of toluene, and the temperature during the supply of oxygen were all changed to 25°C. Carbon black was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1. In addition, using the obtained carbon black, slurry and battery were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0135] [Table 1]
[0136]
[0137] [Table 2]
[0138]
[0139] As shown in Table 1, it was confirmed that when the carbon black of the examples was used, excellent slurry viscosity characteristics and excellent battery characteristics were achieved, and that the carbon black of the present invention could produce a high-performance lithium ion secondary battery with good productivity.
[0140] Industrial Applicability
[0141] The carbon black of the present invention can be preferably used for a slurry for lithium ion secondary battery electrodes and a lithium ion secondary battery.
Claims
1. Carbon black, with a specific surface area of 150m 2 / g above 400m 2 / g or less, DBP absorption is 180mL / 100g or more, the ratio of DBP absorption (DBP) to compressed DBP absorption (CDBP) (DBP / CDBP) is 1.4 or more and 2.0 or less, and the average primary particle size is less than 25nm.
2. The carbon black according to claim 1, wherein The DBP absorption of the carbon black is greater than or equal to 200 mL / 100 g and less than or equal to 350 mL / 100 g.
3. Carbon black according to claim 1 or 2, wherein The carbon black has an ash content of 0.02 mass % or less.
4. The carbon black according to claim 1 or 2, wherein The iron content is less than 2000 mass ppb.
5. The carbon black according to claim 3, wherein The iron content is less than 2000 mass ppb. 6 . A slurry comprising the carbon black according to claim 1 , and a dispersion medium.
7. The slurry according to claim 6, wherein The slurry was heated at 25°C and a shear rate of 10 s -1 The viscosity under the conditions is 200 mPa·s or more and 1200 mPa·s or less.
8. A lithium-ion secondary battery comprising a positive electrode, a negative electrode and a separator, At least one of the positive electrode and the negative electrode contains the carbon black according to any one of claims 1 to 5.
